Remembering the 100,000 lives campaign - Robbins RA (Southwest Journal of Pulmonary and Critical Care, 2016)
No abstract available. Article truncated after 150 words. Earlier this week the Institute for Healthcare Improvement (IHI) emailed its weekly bulletin celebrating that it has been ten years since the end of the 100,000 Lives Campaign (Appendix 1). This was the campaign, according to the bulletin, that put IHI on the map. The Campaign started at the IHI National Forum in December 2004, when IHI's president, Don Berwick, announced that IHI would work together with nearly three-quarters of the US hospitals to reduce needless deaths by 100,000 over 18 months. A phrase borrowed from political campaigns became IHI's cri de coeur: “Some is not a number. Soon is not a time.” The Campaign relied on six key interventions: Rapid Response Teams; Improved Care for Acute Myocardial Infarction; Medication Reconciliation; Preventing Central Line Infections; Preventing Surgical Site Infections; Preventing Ventilator-Associated Pnemonia [sic]. According to the bulletin, the Campaign’s impact rippled across the organization and the world. IHI listed some ...